GENDER-BASED LANGUAGE VARIATIONS IN THE LAST OF US 2 VIDEO GAME - Nadia Ade Arbella; Putu Ayu Asty Senja Pratiwi; I Made Rajeg (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Abstract: The discussion of linguistic features and its relations to gender has been taken into various scientific studies as it further portrayed how men and women implement their language. This study especially aimed to determine the linguistic variations and the differences between men and women language represented through the characters in The Last of Us 2 video game. This study applied qualitative research method to present the data. Moreover, the guiding theory of women and men language by Coates (2013) was used in this study. The result of this study consisted of several points. The first result showed that the linguistic variations in terms of conversational strategies used by the male and female characters in the game are minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo language, and compliments. Meanwhile, the second result discovered the differences from the use of conversational strategies between women and men. The differences laid on the purposes and impressions aimed separately as women tend to soften their utterances while men tend to come off stronger. Therefore, men and women do not differ in terms of the conversational strategies, but the purposes and impressions of both parties contrast significantly.